THE IMPLEMENTATION OF PROBLEM-BASED LEARNING (PBL) MODEL ON THE TOPIC OF FACTORS AFFECTING CHEMICAL EQUILIBRIUM - Sari, Maini Sari; Rusman, Rusman; Hanum, Latifah (Universitas Syiah Kuala, 2024)
The research titled